Quartz powder modifier, preparation method thereof and preparation method of modified quartz powder

By using the combination of unsaturated polyether, fluorescent whitening agent and water as quartz powder modifiers, the problems of limited oil absorption value and reduced whiteness in the prior art are solved, and high compatibility of modified quartz powder is achieved , dispersibility and stability improve the performance of organic quartz composite materials.

CN119463535APending Publication Date: 2025-02-18CHINA RESOURCES CEMENT TECH RES DEV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597241.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the prior art surface modification of quartz powder, the oil absorption value is limited, and the blue light whiteness of the modified quartz powder will decrease, making it difficult to meet the high-performance needs of organic quartz composite materials.

Method used

The combination of unsaturated polyether, fluorescent whitening agent and water is used as the quartz powder modifier. Through specific mass ratios and process ball milling, the oil absorption value of the modified quartz powder is significantly reduced, the whiteness is increased, and it is improved in organic matrix. compatibility, dispersion and stability.

Benefits of technology

The oil absorption value of quartz powder has been significantly reduced, the whiteness and compatibility of modified quartz powder have been improved, the amount of unsaturated resin is reduced, and the performance of organic quartz composite materials has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127252430000091
    Figure BDA0005127252430000091
  • Figure BDA0005127252430000101
    Figure BDA0005127252430000101
Patent Text Reader

Abstract

The invention relates to the technical field of powder surface modification, in particular to a quartz powder modifier, a preparation method thereof and a preparation method of modified quartz powder. The invention provides a quartz powder modifier. The quartz powder modifier comprises unsaturated polyether, a fluorescent whitening agent and water in a mass ratio of (20-40): (0.1-3): (57-79.9), the structural general formula of the unsaturated polyether is as follows: CH2 = CH-R-(OCH2CH2) nOH, CH2 = C (CH3)-R-(OCH2CH2) nOH or CH2 = CH-OR-(OCH2CH2) nOH; in the formula, n is an integer greater than or equal to 0, and R is selected from one of C0-C4 alkyl groups. The quartz powder modifier disclosed by the invention can be used for effectively performing surface modification on quartz powder, reducing the oil absorption value and improving the whiteness; therefore, the compatibility, dispersity and stability of the quartz powder in an organic matrix are effectively improved, and the dosage of unsaturated resin is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder surface modification, in particular to a quartz powder modifier and a preparation method thereof and a preparation method of modified quartz powder. Background Art

[0002] Quartz powder is widely used in organic / inorganic composite materials such as organic quartz stone, wear-resistant floor paint, tire products, functional plastics, etc. due to its low price, white color, abundant resources and good comprehensive performance. It is a widely used non-metallic mineral filler.

[0003] When unmodified quartz powder is directly used in organic quartz stone as an inorganic filler, it is not ideal in many cases. This is mainly because the surface of natural quartz powder is highly polar, and it has poor affinity with polymer materials. When used as a filler, it is unevenly dispersed and easily agglomerated, which increases the resin dosage and causes local deviations in the quartz stone and resin content, which has a great impact on the physical and chemical properties of the product.

[0004] The oil absorption of powder (oil absorption value) is an important indicator of the compatibility of inorganic powder in organic matrix. Surface modification of quartz powder can significantly reduce its oil absorption value, which can change the surface properties of quartz powder, increase its surface affinity with organic matrix, improve compatibility, dispersibility and stability with organic matrix, etc., and achieve performance enhancement of unsaturated resin composite materials. At the same time, it can increase the filling amount of quartz powder, reduce production costs, and save resin. It is of great significance to the high-quality development of organic composite materials industries such as organic quartz stone, functional plastics, tire products, and wear-resistant coatings.

[0005] In the prior art, silane coupling agents, titanic acid coupling agents, stearic acid, etc. are used for surface modification of quartz powder, or a strategy of compounding them is adopted; the addition amount is often high, and the overall reduction in oil absorption value is limited. At the same time, the blue light whiteness of the modified quartz powder prepared by the above-mentioned modifiers will decrease to varying degrees; therefore, it is of great significance to develop or research a modifier that can further significantly reduce the oil absorption value of quartz powder while not reducing or further improving the blue light whiteness of the modified quartz powder, so that it can be better used in the preparation of organic quartz composite materials.

[0006] In view of this, this invention is proposed. Summary of the invention

[0007] The first object of the present invention is to provide a quartz powder modifier, which can effectively modify the surface of quartz powder, reduce the oil absorption value, and increase the whiteness, thereby effectively improving the compatibility, dispersibility and stability of quartz powder in an organic matrix.

[0008] The second object of the present invention is to provide a method for preparing a quartz powder modifier, which has simple steps and is suitable for industrial production.

[0009] The third object of the present invention is to provide a method for preparing modified quartz powder, which can produce modified quartz powder with good modification effect, low oil absorption value and excellent powder whiteness performance.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, the present invention provides a quartz powder modifier, comprising: an unsaturated polyether, a fluorescent brightener and water;

[0012] The mass ratio of the unsaturated polyether, the fluorescent whitening agent and the water is (20-40): (0.1-3): (57-79.9);

[0013] The general structural formula of the unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2) n OH; wherein n is an integer greater than or equal to 0, and R is selected from one of C0 to C4 alkyl groups.

[0014] Furthermore, the mass ratio of the unsaturated polyether, the fluorescent whitening agent and the water is (20-40): (0.5-3): (57-79.5).

[0015] Furthermore, the unsaturated polyether includes at least one of allyl polyoxyethylene ether, methyl allyl polyoxyethylene ether, isopentanol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene alcohol ether, ethylene glycol monovinyl polyoxyethylene glycol ether and 4-hydroxybutyl vinyl polyoxyethylene ether.

[0016] Furthermore, the molecular weights of the allyl polyoxyethylene ether, the methyl allyl polyoxyethylene ether and the isopentanol polyoxyethylene ether are independently 1000 to 3000.

[0017] Furthermore, the molecular weights of the ethylene glycol monovinyl polyoxyethylene alcohol ether, the ethylene glycol monovinyl polyoxyethylene glycol ether and the 4-hydroxybutyl vinyl polyoxyethylene ether are each independently 2000 to 3000.

[0018] Furthermore, the fluorescent whitening agent includes one or more of disodium 4,4'-bis(2-sulfonatostyryl)biphenyl, sodium 4,4'-bis(2-sulfonatostyryl)biphenyl and sodium 2,2'-([1,1'-biphenyl]-4,4'-diylbis(ethylene-2,1-diyl))dibenzenesulfonate.

[0019] In a second aspect, the present invention also provides a method for preparing the quartz powder modifier as described above, comprising the following steps:

[0020] The components are mixed evenly to obtain the quartz powder modifier.

[0021] In a third aspect, the present invention further provides a method for preparing modified quartz powder, wherein the quartz material is modified by using the quartz powder modifier as described above.

[0022] Furthermore, the mass of the quartz powder modifier is 0.1% to 1.0% of the mass of the quartz material.

[0023] Furthermore, the mass of the quartz powder modifier is 0.5% to 1.0% of the mass of the quartz material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The quartz powder modifier provided by the present invention can effectively perform surface modification on quartz powder, has good modification effect, reduces the oil absorption value of quartz powder, and increases the whiteness of quartz powder, thereby effectively improving the compatibility, dispersibility and stability of quartz powder in an organic matrix.

[0026] The modified quartz powder modified by the quartz powder modifier of the present invention has low oil absorption value, excellent powder whiteness performance, good compatibility, dispersibility and stability in the organic matrix, so that the amount of unsaturated resin can be reduced while the performance of the unsaturated resin quartz stone composite material is enhanced. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] The following is a detailed description of a quartz powder modifier and a preparation method thereof and a preparation method of modified quartz powder of the present invention.

[0029] In some embodiments of the present invention, a quartz powder modifier is provided, comprising: an unsaturated polyether, a fluorescent brightener and water;

[0030] The mass ratio of unsaturated polyether, fluorescent whitening agent and water is (20-40): (0.1-3): (57-79.9);

[0031] The general structural formula of unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2) n OH; wherein n is an integer greater than or equal to 0, and R is selected from one of C0 to C4 alkyl groups.

[0032] The quartz powder modifier provided by the present invention can effectively perform surface modification on quartz powder, has good modification effect, reduces the oil absorption value of quartz powder, and increases the whiteness of quartz powder, thereby effectively improving the compatibility, dispersibility and stability of quartz powder in an organic matrix.

[0033] The quartz powder modifier of the present invention contains multiple active groups such as carbon-carbon double bonds, ether bonds, and hydroxyl groups. When the quartz raw material is subjected to the mechanical force of ball milling, the solid material is broken and lattice defects are caused. New interfaces are continuously generated, the internal energy of the solid material is increased, and the Si-O bonds are broken. Higher active points are generated on the surface, making it in an unstable chemically active state, and it is easy to undergo grafting reaction and adsorption and encapsulation with the active groups in the modifier. Compared with silane coupling agents, unsaturated polyethers have larger molecular weights and longer molecular chains, and produce steric hindrance between quartz powders, which increases steric repulsion and further improves the dispersibility of quartz powder; thereby effectively improving the compatibility, dispersibility and stability of quartz powder in an organic matrix; at the same time, adding a certain amount of fluorescent whitening agent to the formula of the quartz powder modifier can improve the whiteness of the quartz powder.

[0034] The modified quartz powder obtained by modification with the quartz powder modifier of the present invention has organic groups grafted and wrapped on the surface, and the surface polarity changes from polar to non-polar, so that it can be effectively dispersed independently in the organic medium, is well compatible with the matrix resin, and can reduce the amount of resin used while maintaining a good material state and performance.

[0035] In the molecular structure of the unsaturated polyether, n represents the degree of polymerization, which is the addition number of ethylene oxide, that is, the number of ethylene oxide groups in the unsaturated polyether molecule, which may vary with the degree of polymerization of polyethylene glycol and the type of enol; R is a C0~C4 alkyl group, which may be a straight-chain alkyl group or a branched-chain alkyl group.

[0036] In different embodiments of the present invention, the mass ratio of unsaturated polyether to fluorescent whitening agent can be 20:0.1, 30:0.1, 40:0.1, 20:0.5, 30:0.5, 40:0.5, 20:1, 30:1, 40:1, 20:2, 30:2, 20:3, 30:3, 40:3 or a range consisting of any two of them; the mass ratio of unsaturated polyether to water can be 20:79.9, 30:68, 35:62.5, 40:57 or a range consisting of any two of them.

[0037] In some embodiments of the present invention, the mass ratio of unsaturated polyether, fluorescent whitening agent and water is (20-40): (0.5-3): (57-79.5).

[0038] In some embodiments of the present invention, the unsaturated polyether includes allyl polyoxyethylene ether (CH2=CHCH2(OCH2CH2) n OH), methyl allyl polyoxyethylene ether (CH2=C(CH3)CH2(OCH2CH2) n OH), isopentanol polyoxyethylene ether (CH2=C(CH3)CH2CH2O(CH2CH2O) n OH), at least one of ethylene glycol monovinyl polyoxyethylene alcohol ether, ethylene glycol monovinyl polyoxyethylene glycol ether and 4-hydroxybutyl vinyl polyoxyethylene ether.

[0039] In some embodiments of the present invention, the molecular weight of allyl polyoxyethylene ether is 1000-3000, the molecular weight of methyl allyl polyoxyethylene ether is 1000-3000, and the molecular weight of isopentanol polyoxyethylene ether is 1000-3000; the molecular weight of ethylene glycol monovinyl polyoxyethylene alcohol ether is 2000-3000, the molecular weight of ethylene glycol monovinyl polyoxyethylene glycol ether is 2000-3000, and the molecular weight of 4-hydroxybutyl vinyl polyoxyethylene ether is 2000-3000.

[0040] In some embodiments of the present invention, the fluorescent whitening agent includes one or more of disodium 4,4'-bis(2-sulfonatostyryl)biphenyl, sodium 4,4'-bis(2-sulfonate styryl)biphenyl (brightener CBS-X) and sodium 2,2'-([1,1'-biphenyl]-4,4'-diylbis(ethylene-2,1-diyl))dibenzenesulfonate.

[0041] In some embodiments of the present invention, a method for preparing the above-mentioned quartz powder modifier is also provided, comprising the following steps:

[0042] The components are mixed to obtain a quartz powder modifier.

[0043] In some embodiments of the present invention, a method for preparing modified quartz powder is also provided, wherein the quartz material is modified by using the above-mentioned quartz powder modifier.

[0044] In some embodiments of the present invention, the mass of the quartz powder modifier is 0.1% to 1.0% of the mass of the quartz material; typically but not limiting, for example, the mass of the quartz powder modifier is 0.1%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% of the mass of the quartz material or a range of any two thereof.

[0045] In some preferred embodiments of the present invention, the mass of the quartz powder modifier is 0.5% to 1.0% of the mass of the quartz material.

[0046] In some embodiments of the present invention, the quartz material includes but is not limited to quartz sand.

[0047] In some embodiments of the present invention, the method for preparing modified quartz powder specifically comprises the following steps:

[0048] The quartz powder modifier is evenly added to the quartz sand (particle size of 40-120 mesh) on the conveyor belt through a T-shaped porous tube by a metering pump, and then transported to a premixer for mixing, and then enters a ball mill for ball milling at 80-90°C for 6-10 minutes. After air separation, modified quartz powder is obtained.

[0049] Example 1

[0050] The preparation method of the quartz powder modifier provided in this embodiment comprises the following steps:

[0051] The unsaturated polyether (methyl allyl polyoxyethylene ether, HPEG-2400), the brightener CBS-X and water were mixed in a mass ratio of 0.3:0.01:0.69 to obtain a quartz powder modifier.

[0052] The method for preparing the modified quartz powder provided in this embodiment comprises the following steps:

[0053] The quartz powder modifier of this embodiment is evenly added dropwise to the quartz sand (particle size of 40 to 120 mesh) on the conveyor belt through a T-shaped porous tube by a metering pump. The mass of the quartz powder modifier is 0.5% of the mass of the quartz sand. The quartz powder modifier is then transported to a premixer for mixing, and then enters a ball mill for ball milling at 85° C. for 8 minutes. After air separation, modified quartz powder with a particle size of 325 mesh is obtained.

[0054] Example 2

[0055] The preparation method of the quartz powder modifier provided in this embodiment refers to Example 1, except that the unsaturated polyether is prenol polyoxyethylene ether (TPEG-2400).

[0056] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0057] Example 3

[0058] The preparation method of the quartz powder modifier provided in this embodiment refers to Example 1, except that the unsaturated polyether is methyl allyl polyoxyethylene ether (HPEG-2400) and isopentanol polyoxyethylene ether (TPEG-2400) in a mass ratio of 1:1.

[0059] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0060] Example 4

[0061] The preparation method of the quartz powder modifier provided in this embodiment refers to Example 1, except that the unsaturated polyether is ethylene glycol monovinyl polyoxyethylene glycol ether (molecular weight is 2000-3000).

[0062] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0063] Example 5

[0064] The preparation method of the quartz powder modifier provided in this embodiment refers to Example 1, except that the unsaturated polyether is 4-hydroxybutyl vinyl polyoxyethylene ether (molecular weight is 2000-3000).

[0065] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0066] Example 6

[0067] The preparation method of the quartz powder modifier provided in this embodiment comprises the following steps:

[0068] The unsaturated polyether (methyl allyl polyoxyethylene ether, HPEG-2400), the brightener CBS-X and water were mixed in a mass ratio of 0.2:0.005:0.795 to obtain a quartz powder modifier.

[0069] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0070] Example 7

[0071] The preparation method of the quartz powder modifier provided in this embodiment comprises the following steps:

[0072] The unsaturated polyether (methyl allyl polyoxyethylene ether, HPEG-2400), the brightener CBS-X and water were mixed in a mass ratio of 0.4:0.03:0.57 to obtain a quartz powder modifier.

[0073] The preparation method of the modified quartz powder provided in this embodiment refers to Example 1.

[0074] Example 8

[0075] The preparation method of the modified quartz powder provided in this embodiment refers to that in Example 1, the only difference is that the mass of the quartz powder modifier is 0.1% of the mass of the quartz sand.

[0076] Example 9

[0077] The preparation method of the modified quartz powder provided in this embodiment refers to that of Example 1, except that the mass of the quartz powder modifier is 1.0% of the mass of the quartz sand.

[0078] Comparative Example 1

[0079] The quartz powder modifier provided in this comparative example is silane coupling agent KH560.

[0080] The preparation method of the modified quartz powder provided in this comparative example is referenced to Example 1.

[0081] Comparative Example 2

[0082] The quartz powder modifier provided in this comparative example is silane coupling agent KH570.

[0083] The preparation method of the modified quartz powder provided in this comparative example is referenced to Example 1.

[0084] Test example

[0085] The properties of the modified quartz powders obtained in Examples 1 to 9 and Comparative Examples 1 to 2 and the unmodified quartz powders with a particle size of 325 mesh were tested, and the results are shown in Table 1.

[0086] The test method of oil absorption value is: weigh the sample and place it on a clean glass plate with an area of ​​not less than 200mm×200mm, then use an acid burette with precision of Class A to load the oil (unsaturated polyester resin); use the acid burette to slowly drip the oil into the sample while constantly stirring with a glass rod so that the sample and the oil are evenly mixed. The detection end point is: when the last drop is added, the sample and the oil just stick together into a ball, and there is no free dry sample. The calculation formula of oil absorption value is: A0=V / M(mL / g); where A0 is the oil absorption value; V is the volume of the oil used; M is the mass of the sample.

[0087] The whiteness test method is: use a whiteness meter to test the whiteness of the sample, and the operation method follows the equipment and instrument operating procedures.

[0088] The test method for the amount of resin is: the formula of quartz powder fine particle board is used for determination, and the material ratio of sand and powder of the fine particle board is as follows: quartz sand with a particle size of 40-70 mesh: quartz sand with a particle size of 70-120 mesh: quartz powder with a particle size of 325 mesh or modified quartz powder with a particle size of 325 mesh is 4:3:3; when testing the amount of resin, weigh the sand and powder materials according to the above ratio, put them in a mixer, add unsaturated polyester resin while stirring, until the material state can be pressed into shape, the curing agent dosage is 1% of the unsaturated polyester resin dosage, and the mass of the unsaturated polyester resin at this time divided by the total weight of the material is the required resin dosage.

[0089] Table 1

[0090]

[0091]

[0092] It can be seen from Table 1 that after modification with the quartz powder modifier of the present invention, the oil absorption value of the quartz powder is significantly reduced, thereby effectively improving the compatibility, dispersibility and stability of the quartz powder in the organic matrix, achieving the performance enhancement of the unsaturated resin quartz stone composite material, while reducing the amount of unsaturated resin and reducing the production cost.

[0093] Comparison of Example 1, Comparative Example 2 and unmodified quartz powder shows that, compared with the existing modifier, the modification effect of the quartz powder modifier of the present invention is greatly improved, the oil absorption value of the modified quartz powder is reduced from 22.5% to 20.5%, the reduction rate of the amount of organic quartz resin is increased from 1.5% to 2.0%, and the whiteness of the modified quartz powder is improved.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A quartz powder modifier, characterized in that: include: Unsaturated polyether, fluorescent brightener and water; The mass ratio of the unsaturated polyether, the fluorescent whitening agent and water is (20-40): (0.1-3): (57-79.9); The general structural formula of the unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2) n OH; wherein n is an integer greater than or equal to 0, and R is selected from one of C0 to C4 alkyl groups.

2. The quartz powder modifier according to claim 1, characterized in that The mass ratio of the unsaturated polyether, the fluorescent whitening agent and the water is (20-40): (0.5-3): (57-79.5).

3. The quartz powder modifier according to claim 1, characterized in that The unsaturated polyether includes at least one of allyl polyoxyethylene ether, methyl allyl polyoxyethylene ether, isopentanol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene alcohol ether, ethylene glycol monovinyl polyoxyethylene glycol ether and 4-hydroxybutyl vinyl polyoxyethylene ether.

4. The quartz powder modifier according to claim 3, characterized in that The molecular weights of the allyl polyoxyethylene ether, the methyl allyl polyoxyethylene ether and the isopentanol polyoxyethylene ether are each independently 1000 to 3000.

5. The quartz powder modifier according to claim 3, characterized in that The molecular weights of the ethylene glycol monovinyl polyoxyethylene alcohol ether, the ethylene glycol monovinyl polyoxyethylene glycol ether and the 4-hydroxybutyl vinyl polyoxyethylene ether are each independently 2000 to 3000.

6. The quartz powder modifier according to claim 3, characterized in that The fluorescent whitening agent includes one or more of disodium 4,4'-bis(2-sulfonatostyryl)biphenyl, sodium 4,4'-bis(2-sulfonatostyryl)biphenyl and sodium 2,2'-([1,1'-biphenyl]-4,4'-diylbis(ethylene-2,1-diyl))dibenzenesulfonate.

7. The method for preparing the quartz powder modifier according to any one of claims 1 to 6, characterized in that: The steps include: The components are mixed evenly to obtain the quartz powder modifier.

8. A method for preparing modified quartz powder, characterized in that: The quartz material is modified by using the quartz powder modifier described in any one of claims 1 to 6.

9. The method for preparing modified quartz powder according to claim 8, characterized in that: The mass of the quartz powder modifier is 0.1% to 1.0% of the mass of the quartz material.

10. The method for preparing modified quartz powder according to claim 8, characterized in that: The mass of the quartz powder modifier is 0.5% to 1.0% of the mass of the quartz material.